Prognosis of patients with syncope seen in the emergency room department: an evaluation of four different risk scores recommended by the European Society of Cardiology guidelines. (December 2017) - Barón-Esquivias, Gonzalo; Fernández-Cisnal, Agustín; Arce-León, Álvaro; Toro, Rocio; Cantero-Pérez, Eva; Parejo-Matos, Juan; Romero-Rodriguez, Nieves; Montero, Emilio; Martinez, Angel
Abstract : Aim: To apply, analyze, and evaluate the four syncope risk scores recommended by the 2009 European guidelines and the different parameters that they use to predict death, syncope recurrence, and hospital readmission in the population seen in the emergency room department (ERD) for syncope. Methods and results: A total of 323 patients aged older than 14 years [mean age 59 (32–75) years] and seen in ERD for syncope over a 2-month period were included in the study; 50.7% were women. Patients were evaluated using the four risk scores and were followed up for at least 2 years. In all, 275 patients (85.2%) were discharged directly from ERD after evaluation. During 28±5 months of follow-up, 8% died, 18.3% presented a further syncopal episode, and 18.6% were readmitted to hospital. Only two of the four risk scores were useful in risk discrimination, but no statistically significant differences were detected between predicted risk and observed risk. Multivariate analysis indicated relationships between age and death, a history of cardiovascular disease and syncope recurrence, and between presyncopal palpitations and hospital readmission. Conclusion: Although a large number of events occur after syncope, the risk scores recommended by guidelines overestimate risk, but there were no statistically significant differences between observed and predicted risk. Abstract : Supplemental Digital Content is available in the text.